2016
DOI: 10.1117/12.2223601
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Raman scattering from persistent chemical warfare agents

Abstract: Laser induced Raman scattering at excitation wavelengths in the middle ultraviolet was examined using a pulsed tunable laser based spectrometer system. Droplets of chemical warfare agents, with a volume of 2 µl, were placed on a silicon surface and irradiated with sequences of laser pulses. The Raman scattering from V-series nerve agents, Tabun (GA) and Mustard gas (HD) was studied with the aim of finding the optimum parameters and the requirements for a detection system. A particular emphasis was put on V-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In particular, Kullander et al found that excitation at 270 nm causes a large peak to appear at 1650 cm –1 and becomes the strongest spectral peak. This feature is absent in the spectrum taken at 330 nm; no such changes were found for sulfur mustard (HD) or Tabun (GA) . These data highlight that the precise choice of laser wavelength can impact the detection of these materials.…”
Section: Applications Of Raman Scattering-based Techniques To Defense...mentioning
confidence: 86%
See 3 more Smart Citations
“…In particular, Kullander et al found that excitation at 270 nm causes a large peak to appear at 1650 cm –1 and becomes the strongest spectral peak. This feature is absent in the spectrum taken at 330 nm; no such changes were found for sulfur mustard (HD) or Tabun (GA) . These data highlight that the precise choice of laser wavelength can impact the detection of these materials.…”
Section: Applications Of Raman Scattering-based Techniques To Defense...mentioning
confidence: 86%
“…Owing to their extreme toxicity, much of the work on CWAs has been conducted on simulant chemicals with similar molecular features, such as organophosphates or on the hydrolysis products of these materials. ,,, It is worth noting that many of simulants used are the same as the hydrolysis products. As such, they remain valuable detection targets in their own right, with the potential to act as markers of the release of CWAs.…”
Section: Applications Of Raman Scattering-based Techniques To Defense...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous experiments 6 0.1 to 1 µl in volume 7 in simplified laboratory conditions. In this work we have only used 1 µl droplets, although detection of much smaller droplets will be possible.…”
Section: Introductionmentioning
confidence: 99%